2012
DOI: 10.5301/jbm.2012.9146
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic relevance of STAT3 and cyclin D1 in non-small cell lung cancer

Abstract: STAT3 might be correlated with tumor differentiation, and its elevated expression may be an adverse prognostic indicator for patients with NSCLC. Activation of the STAT3/cyclin D1 signaling pathway may be attributed to the malignant transformation of NSCLC and may represent a possible target for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Thus, the JAK2/STAT3 pathway is an important therapeutic target for cancer treatment. Moreover, there is a significant association between the JAK2/STAT3 pathway and lung tumor development in the patient [49,50]. Our previous studies demonstrated that bee venom and melittin inhibited the JAK2/ STAT3 pathway, resulting in lung cancer cell growth inhibition [51].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the JAK2/STAT3 pathway is an important therapeutic target for cancer treatment. Moreover, there is a significant association between the JAK2/STAT3 pathway and lung tumor development in the patient [49,50]. Our previous studies demonstrated that bee venom and melittin inhibited the JAK2/ STAT3 pathway, resulting in lung cancer cell growth inhibition [51].…”
Section: Discussionmentioning
confidence: 98%
“…The c-Myc oncoprotein promotes cell cycling progression, plays a vital role in most human cancers (Dang et al , 2006) and cooperates with Mcl-1 in the development of NSCLC (Allen et al ., 2011). Similarly, cyclin D1 is a central player in the cell cycle and plays an essential role in the development of NSCLC (Ai et al ., 2012). Consequently, the down-regulation of Bcl-2, Bclx L , Mcl-1, Survivin, c-Myc and cyclin D1 by CAERS imply that this extract could effectively target the survival advantage provided by these effectors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that upregulated expression of STAT3 is associated with more malignant behavior of tumor cells and worse prognosis in a variety of human malignancies, e.g., cancers of the breast, prostate, ovary, lung, head and neck, esophagus, and brain [53,54,55,56,57,58,59,60,61]. In pancreatic cancer, STAT3 was shown to regulate angiogenesis and metastasis [62] and to promote cellular proliferation by accelerating G1/S-phase progression [63].…”
Section: Jak/stat Signaling In Different Cancer Typesmentioning
confidence: 99%